A Contribution to the Genetic Epidemiology of Structured Populations - Stark, Alan E. (International Journal of Statistics in Medical Research, 2015)
A mating system, previously derived, which is more general than random mating is defined by the gene frequency q and a parameter F which measures divergence from Hardy-Weinberg proportions commonly used in genetic analysis. F can be viewed as the average coefficient of inbreeding in a population, the use emphasized here. Also it can characterize the variation in gene frequency in a stratified population. Taking q as fixed, the distribution of F over values admissible under the general mating system is derived by simulation. The mating system may be seen to be based on indifference as to choice of mates. This is the first object of the paper. The second uses the derived distribution of F to make a Bayesian estimate of F from a single sample of genotypic counts. Such an estimate has a number of uses in genetic analysis.